The Pleistocene species pump past its prime: Evidence from European butterfly sister species. Issue 14 (2nd June 2021) - Ebdon, Sam; Laetsch, Dominik R.; Dapporto, Leonardo; Hayward, Alexander; Ritchie, Michael G.; Dincӑ, Vlad; Vila, Roger; Lohse, Konrad
Abstract: The Pleistocene glacial cycles had a profound impact on the ranges and genetic make‐up of organisms. While it is clear that the contact zones that have been described for many sister taxa are secondary and have formed in the current interglacial, it is unclear when the taxa involved began to diverge. Previous estimates based on small numbers of loci are unreliable given the stochasticity of genetic drift and the contrasting effects of incomplete lineage sorting and gene flow on gene divergence. Here, we use genome‐wide transcriptome data to estimate divergence for 18 sister species pairs of European butterflies showing either sympatric or contact zone distributions. We find that in most cases, species divergence predates the mid‐Pleistocene transition or even the entire Pleistocene period. We also show that although post‐divergence gene flow is restricted to contact zone pairs, they are not systematically younger than sympatric pairs. This suggests that contact zones are not limited to the initial stages of the speciation process, but can involve notably old taxa. Finally, we show that mitochondrial divergence and nuclear divergence are only weakly correlated and mitochondrial divergence is higher for contact zone pairs.